TYK2 promotes malignant peripheral nerve sheath tumor progression through inhibition of cell death. (6th July 2019) - Qin, Wenjing; Godec, Abigail; Zhang, Xiaochun; Zhu, Cuige; Shao, Jieya; Tao, Yu; Bu, Xianzhang; Hirbe, Angela C.
Abstract: Background: Malignant peripheral nerve sheath tumors (MPNSTs) are aggressive sarcomas that arise most commonly in the setting of the Neurofibromatosis Type 1 (NF1) cancer predisposition syndrome. Despite aggressive multimodality therapy, outcomes are dismal and most patients die within 5 years of diagnosis. Prior genomic studies in our laboratory identified tyrosine kinase 2 ( TYK2 ) as a frequently mutated gene in MPNST. Herein, we explored the function of TYK2 in MPNST pathogenesis. Methods: Immunohistochemistry was utilized to examine expression of TYK2 in MPNSTs and other sarcomas. To establish a role for TYK2 in MPNST pathogenesis, murine and human TYK2 knockdown and knockout cells were established using shRNA and CRISPR/Cas9 systems, respectively. Results: We have demonstrated that TYK2 was highly expressed in the majority of human MPNSTs examined. Additionally, we demonstrated that knockdown of Tyk2/TYK2 in murine and human MPNST cells significantly increased cell death in vitro. These effects were accompanied by a decrease in the levels of activated Stats and Bcl‐2 as well as an increase in the levels of Cleaved Caspase‐3. In addition, Tyk2 ‐KD cells demonstrated impaired growth in subcutaneous and metastasis models in vivo. Conclusion: Taken together, these data illustrate the importance of TYK2 in MPNST pathogenesis and suggest that the TYK2 pathway may be a potential therapeutic target for these deadly cancers. Abstract : We have demonstrated that Tyk2 knockdown leads to decreased STAT activation and increased cell death in vitro. Additionally, Tyk2 knockdown leads to dramatic decreased in tumor and increased survival in vivo, suggesting that this is a novel target for MPNST treatment.